Isamu Noguchi a production of Whitgate productions, Ltd. (Chicago, Il Home Vision Arts, 1980)
Noguchi travels, sculpts, describing his work and his feelings about it.
VHS format.
Producer, director, writer, Bruce w. Bassett ; director of photography, Bruce G. Sparks ; editor, John J. Martin ; music supervisors, Crosby Williams.
Bruce W. Bassett
Keywords: Noguchi, Isamu, 1904-1988.; Sculptors -- Japan -- Biography; Sculptors -- United States -- Biography